Хто такий Салур Казан? - Ахмет Ержілясун (Народна творчість та етнографія, 2010)
In this article, the period of the facts and persons of Dede Korkut’s book was researched. It was resulted that the facts and persons in the book were lived in the Turgish period and Salur Kazan was Su-lu Kagan. According to the Chineese sources, Su-lu Kagan has not divided up the loot and, in the same way, Salur Kazan also has not divided up the loot.